The Essence of The Philosophy "Vahdat Ul Vujud" In the Teaching of Sufism - S. Karimov (Periodica Journal, 2022)
The article explains the essence of the philosophy of "unity and being", which is the doctrine of unity and oneness in mysticism
Keywords: unity; existence; love; manifestation